Строки судьбы: сонеты / Александр Гребенкин ; [художник В. В. Злобин] - Гребенкин Александр Алексеевич (Форвард-С, 2016)
Экземпляры: ф.1 (20161124) / Инвентарный номер: 57272 / Сис.шифр: 84(2Рос=Удм)6-5 / Авт.знак: Г 79 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Удм)6-5